Impact of Fasting Mimicking Diet (FMD) on cardiovascular risk factors: a systematic review and meta-analysis of randomized control trials - Milad Mohammadzadeh; Mahdi Amirpour; Hamid Ahmadirad; Fatemeh Abdi; Saman Khalesi; Niayesh Naghshi; Alireza Bahrami; Ehsan Hejazi (Diabetology & Metabolic Syndrome)
Abstract Introduction The Fasting Mimicking Diet (FMD) has gained significant attention as a potential intervention for reducing cardiovascular risk factors. While studies have investigated its effectiveness, findings have been inconsistent. Therefore, this systematic review and meta-analysis aimed to clarify evidence on the impact of FMD on cardiovascular risk factors. Method PubMed, Web of Science, Scopus, and Google Scholar were searched for eligible Randomized controlled trials (RCTs) published up to July 2024. Weighted mean differences (WMD) were calculated for the net changes in risk factors using random-effects models. Results Eleven RCTs (with twelve treatment arms) were included. FMD significantly reduced glycated hemoglobin (HbA1c) (WMD = -8.589 mmol/mol, 95% CI: −12.389, -4.769), insulin-like growth factor 1 (IGF-1) (WMD= -19.211 ng/ml, 95% CI: −32.986, -5.437), systolic blood pressure (SBP) (WMD = -4.148 mmHg, 95% CI: −7.584, -0.711), and diastolic blood pressure (DBP) (WMD = -2.263 mmHg, 95% CI: −4.162, -0.364) levels. No significant effects were observed on other cardiovascular risk factors. Conclusion This meta-analysis suggests that FMD can significantly reduce HbA1c, IGF-1, SBP, and DBP levels. Further research is warranted to investigate the long-term and potential clinical implications of FMD on cardiovascular health. Prospero registration The protocol of the study was registered in the International Prospective Register of Systematic Reviews (PROSPERO registration no: CRD42024569426).